1997
DOI: 10.1038/sj.onc.1200964
|View full text |Cite|
|
Sign up to set email alerts
|

Cloning of human bone morphogenetic protein type IB receptor (BMPR-IB) and its expression in prostate cancer in comparison with other BMPRs

Abstract: Bone metastasis is a common event in prostate cancer, and it is known that some of the bone morphogenetic proteins (BMPs) are expressed in prostate cancer cells, while no study on the expression of their receptors, BMPRs, has been reported. Here we report cloning and sequence analysis of the human BMPR-IB cDNA. We also analysed the expression of transcripts of three types of the BMPR genes in human tissues and prostate cancer cell lines. The BMPR-IB mRNA was present in various organs, but the highest level was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…LIF gene expression occurs at di erent stages of development, usually at very low levels (data not shown). Comparing with a standard cDNA library screening method, our modi®ed cDNA selection method was shown to be more e ective for cloning a cDNA derived from a transcript whose expression level was too low to be detected by Northern blot analysis (Ide et al, 1997;Kishi et al, 1997;. Thus, our modi®ed cDNA selection method was used for isolation of a rat LIF cDNA clone containing complete coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…LIF gene expression occurs at di erent stages of development, usually at very low levels (data not shown). Comparing with a standard cDNA library screening method, our modi®ed cDNA selection method was shown to be more e ective for cloning a cDNA derived from a transcript whose expression level was too low to be detected by Northern blot analysis (Ide et al, 1997;Kishi et al, 1997;. Thus, our modi®ed cDNA selection method was used for isolation of a rat LIF cDNA clone containing complete coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with a later study by Hamdy et al (25), who reported that BMP-6 mRNA expression was detected exclusively in malignant epithelial cells in 20 of 21 patients (95%) with metastases, in 2 of 11 patients (18%) with localized cancer, and undetectable in 8 benign samples. In addition to BMP, there have been several reports on prostate cancer expression of BMPR; it seems that as prostate cancer progress, the cells down-regulate their own expression of BMPRs (50,51), which may be a protective mechanism as it has been shown that BMP-2 can inhibit prostate cancer cell proliferation (52). Taken together, these observations show that prostate cancer cells produce increasing levels of BMPs as they progress to a more aggressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Among the BMP type I receptors, ALK3 and ALK6 are notable in that they share significant structural homology, with 85% identity in their kinase domain and 42% identity in their extracellular domain (Ide et al, 1997). In particular, the two receptors possess identical glycine-serine (GS)-rich domains and L45 loops, known structural elements essential for their kinase activation and Smad recognition, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The type II receptor in turn transphosphorylates the type I receptor activating its kinase activity. Subsequently, the type I receptors engage and phosphorylate their intracellular effectors, the BMP-responsive Smads (Smad1, -5, and -8), which upon phosphorylation, complex with Smad4 and accumulate in the nucleus to regulate the transcription of target genes.Among the BMP type I receptors, ALK3 and ALK6 are notable in that they share significant structural homology, with 85% identity in their kinase domain and 42% identity in their extracellular domain (Ide et al, 1997). In particular, the two receptors possess identical glycine-serine (GS)-rich domains and L45 loops, known structural elements essential for their kinase activation and Smad recognition, respectively.…”
mentioning
confidence: 99%